Weather Conditions and Economic Growth - Is Productivity Hampered by Climate Change? - Thomas Brenner; Daniel Lee (Philipps-University Marburg, Department of Geography, 2014)
Climate change researchers predict a dramatic increase in global average temperature over the next decades. We use past temperature and precipitation fluctuations to investigate whether changes in temperature and precipitation are associated with decreases in economic growth. A GMM panel regression is used to analyze the effects of the average yearly heat index and precipitation on economic growth in 105 countries for the time period 1991-2009.
Keywords: O11; O13; E10; C23; 330; national growth; heat; average yearly temperature; growth effects; panel GMM